2016
DOI: 10.3390/polym8030053
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability of Emulsions in Preparation of Uniform Small-Sized Konjac Glucomanna (KGM) Microspheres with Epoxy-Based Polymer Membrane by Premix Membrane Emulsification

Abstract: Uniform small-sized (<10 µm) Konjac glucomanna (KGM) microspheres have great application prospects in bio-separation, drug delivery and controlled release. Premix membrane emulsification is an effective method to prepare uniform small-sized KGM microspheres. However, since KGM solution bears strong alkalinity, it requires the membrane to have a hydrophobic surface resistant to alkali. In this study, uniform small-sized KGM microspheres were prepared with epoxy-based polymer membrane (EP) we developed by premix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Zhang et al [14] fabricated an ultralow oil-fouling amphiphilic copolymer incorporated poly(ether sulfone) (PES) heterogeneous membrane. First, the amphiphilic copolymer was prepared by semibatch reversible addition-where the fragmentation chain was transferred by poly (ethylene glycol) methyl ether methacrylate (PEGMA) and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate (TFOA). The resultant amphiphilic fluorinated gradient copolymers were then incorporated into the PES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [14] fabricated an ultralow oil-fouling amphiphilic copolymer incorporated poly(ether sulfone) (PES) heterogeneous membrane. First, the amphiphilic copolymer was prepared by semibatch reversible addition-where the fragmentation chain was transferred by poly (ethylene glycol) methyl ether methacrylate (PEGMA) and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate (TFOA). The resultant amphiphilic fluorinated gradient copolymers were then incorporated into the PES.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed various types of microfilters. Membranes are the most important part of the microfiltration process [ 8 ]. For instance, it was found that superhydrophilic in situ-crosslinked zwitterionic polyelectrolyte/polyvinylidene fluoride-blend membranes exhibit high water permeation flux and good antifouling properties for separating oil-in-water emulsions with high separation efficiency [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without the presence of amphiphilic compounds coalescence and flocculation may take place in emulsions, most of which during storage, resulting in phase separation which lead the system to loose its functionality and acceptance (Agama-Acevedo and Bello-Perez, 2017, Mi et al, 2016). To be a good emulsifying agent, a material must own an interfacial property.…”
Section: Osa Starch Forms a Stable Emulsion Systemmentioning
confidence: 99%
“…Furthermore, difference in size of the microspheres could be related to the stability of the emulsion in the solution. According to Mi et al [18], the stability of the emulsion was related to the interface energy between the polymer and the emulsifier. Flocculation between the microspheres can be avoided by reducing the interface energy.…”
Section: Microstructural Analysismentioning
confidence: 99%